Temperature sensitivity analysis of dopingless charge-plasma transistor. (March 2016) - Shrivastava, Vishwas; Kumar, Anup; Sahu, Chitrakant; Singh, Jawar
Abstract: The junctionless field-effect transistors (JLFETs) have shown potential to scale down in sub-10 nm regime due to simplified fabrication process and less short-channel effects (SCEs), however, sensitivity towards process parameter variation is a major concern. Therefore, in this paper, sensitivity towards temperature variation of recently proposed dopingless (DL) double-gate field-effect transistor (DGFET) and JL-DGFET is reported. Different digital and analog performance metrics were considered and compared for both devices of similar geometries. We observed that the drive current of DL-DGFET decreases with temperature, while, it increases in JL-DGFET because both devices are affected by different scattering mechanisms at higher temperature. The variation in I ON and I OFF in DL-DGFET are only 0.095  μ A/K and 0.2  nA / K, respectively, while, in JL-DGFET the changes are 0.25  μ A/K and 0.34  nA / K, respectively, above room temperature. Below room temperature, it was found that the incomplete ionization effect in JL-DGFET severely affects the drive current, however, DL-DGFET remains unaffected. Hence, the proposed DL-DGFET is less sensitive towards temperature variation and can be employed for cryogenics to high temperature applications.